2009
DOI: 10.1128/jcm.01687-08
|View full text |Cite
|
Sign up to set email alerts
|

Unreliable Extended-Spectrum β-Lactamase Detection in the Presence of Plasmid-Mediated AmpC in Escherichia coli Clinical Isolates

Abstract: The emergence of extended-spectrum ␤-lactamase (ESBL) and plasmid-mediated AmpC (pAmpC) enzymes in Escherichia coli raises concern regarding accurate laboratory detection and interpretation of susceptibility testing results. Twenty-six cefpodoxime ESBL screen-positive, cefoxitin-resistant E. coli clinical isolates were subjected to clavulanate ESBL confirmatory testing employing disk augmentation, Etest, and the BD Phoenix NMC/ID-132 panel. Phenotypic pAmpC production was assessed by boronic acid disk augmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 16 publications
1
40
1
4
Order By: Relevance
“…Discrepancy testing of CDT-positive/ LM-PCR-negative isolates confirmed all six LM-PCRnegative results. In three of the six isolates, an AmpC gene was detected (two Enterobacter cloacae and one Escherichia coli combined with a non-ESBL TEM), a b-lactamase hyperproducer with similar patterns of resistance to extendedspectrum cephalosporins such as ESBL that is able to generate false-positive results in phenotypic ESBL tests by producing an increase in the inhibition zone with the combination cephalosporin-clavulanate disc Robberts et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrepancy testing of CDT-positive/ LM-PCR-negative isolates confirmed all six LM-PCRnegative results. In three of the six isolates, an AmpC gene was detected (two Enterobacter cloacae and one Escherichia coli combined with a non-ESBL TEM), a b-lactamase hyperproducer with similar patterns of resistance to extendedspectrum cephalosporins such as ESBL that is able to generate false-positive results in phenotypic ESBL tests by producing an increase in the inhibition zone with the combination cephalosporin-clavulanate disc Robberts et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2001) found that decreased outermembrane permeability, due to loss of outer-membrane protein K35 (OmpK35), and the hydrolytic effect of TEM-1 can increase the MIC of cefotaxim slightly. The addition of clavulanic acid inhibits TEM-1 b-lactamase production and reduces the MIC, causing augmentation of the inhibition zone diameter, resulting in a false-positive ESBL test result (Beceiro et al, 2011;Robberts et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…It is also of note that although the CLSI ESBL confirmatory test showed false-positive results among four non-ESBL-producing isolates, the modified test was negative among all non-ESBL producers of the study. Accordingly, previous surveys have shown that the CLSI ESBL confirmatory test may give a few false-positive results among non-ESBL-, AmpC-producing Enterobacteriaceae, while a modification of the test using BA did not give any false-positive results in this bacterial population (16,38). In addition, among isolates coproducing AmpCs or carbapenems, the proposed modified test provided considerably higher increases in the inhibitory zone diameters around disks containing CAZ or CTX, allowing an easy and straightforward interpretation of the phenotypic test.…”
Section: Discussionmentioning
confidence: 99%
“…Inconclusive cefotaxime-and ceftazidime-based confirmatory tests should be reported as such (and not as ESBL negative) to avoid the risk of reporting false susceptibility to a more potent cephalosporin such as cefepime. Etest confirmatory strips are convenient but expensive and yield more inconclusive results than CLSI tests due to a more restricted concentration range (11,40). Until proven otherwise, confirmed ESBL-producing isolates should be reported as resistant to all penicillins, cephalosporins, and aztreonam (8) to avoid therapy with antibiotics that may be clinically ineffective (6,20,32,38).…”
Section: Manual Confirmatory Testsmentioning
confidence: 99%